Strategic reading 3 - Richards, Jack C. (Cambridge University Press, 2003)
Strategic Reading is a three-level series designed to develop reading, vocabulary-building, and critical-thinking skills. The Student's Book contains 16 thematic units with a selection of engaging topics that motivate learners to relate the reading to their own experiences. Three inviting reading passages in each unit, all adapted from authentic sources, allow students to explore the theme in depth. The original sources expose learners to a wide range of writing styles. Preview pages in every unit introduce new vocabulary and ask thought-provoking questions. Vocabulary-building activities improve students' ability to deal with unfamiliar words, and recycle key vocabulary with challenging exercises and puzzles. Reading topics include superstitions, technology, memory, personality, the media, art, and humor